2019
DOI: 10.1371/journal.ppat.1007814
|View full text |Cite
|
Sign up to set email alerts
|

Accumulating evidence suggests that some waterbird species are potential vectors of Vibrio cholerae

Abstract: Vibrio cholerae is the causative agent of cholera, a life-threatening diarrheal disease. Cholera causes epidemics and pandemics, but the ways this disease spreads worldwide is still unclear. This review highlights a relatively new hypothesis regarding the way V . cholerae can be globally dispersed. Copepods and chironomids are natural reservoirs of V . cholerae and are part of different fish species’ diet. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Besides other Vibrio spp., our results indicated the presence of V. cholerae in both sedentary and migratory birds, but with a higher frequency in migratory birds. Wild birds possess an important role in the epidemiology of Vibrio spp.-associated outbreaks [ 56 , 57 ] due to the particularities of their habitat and the interrelations with human activities (boat fishing, fish processing areas, and shellfish beds). Prolonged survival and persistence of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…Besides other Vibrio spp., our results indicated the presence of V. cholerae in both sedentary and migratory birds, but with a higher frequency in migratory birds. Wild birds possess an important role in the epidemiology of Vibrio spp.-associated outbreaks [ 56 , 57 ] due to the particularities of their habitat and the interrelations with human activities (boat fishing, fish processing areas, and shellfish beds). Prolonged survival and persistence of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…Using cloning methods, Ryu et al (2014) showed that migratory shorebirds are potential reservoirs of pathogenic Campylobacter species. Halpern et al (2008) suggested that migratory waterbirds are able to disseminate Vibrio cholerae , and explained the dispersal in that some waterbird species feed on copepods, chironomids and/or fish, all of which are reservoirs of the cholera bacterium (Laviad-Shitrit et al, 2019). Halpern and Senderovich (2015) suggested a novel concept regarding the predator–prey scenario.…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic environments, V. cholerae cells are associated with zooplankton, particularly copepods (Huq et al., 1983) and chironomids (Broza & Halpern, 2001; Halpern et al., 2006). Recent evidence also supports the hypothesis that fish and waterbirds may be intermediate V. cholerae reservoirs and may promote its dispersal (Halpern & Izhaki, 2017; Hounmanou et al., 2019; Laviad‐Shitrit et al., 2018, 2019; Mitchell et al., 2017; Runft et al., 2014; Senderovich et al., 2010; Xu et al., 2019; Zago et al., 2017).…”
Section: Introductionmentioning
confidence: 53%